Coal logistics node location method based on analytic hierarchy process - Zhang, Shu; Zhu, L. (2015)
©, 2015, Nanjing University of Science and Technology. All right reserved. To decrease the circulation cost of supply chain, shorten transportation route, quicken system response speed and promote the cooperation of production and consumption, a coal logistics node location method based on analytic hierarchy process is proposed with comprehensive analysis from business, customer and regional plan perspectives. A coal node location hierarchical model is established with natural and social factors as main criterions. An optimum site-selection scheme is obtained by analyzing three given site-selection schemes using analytical hierarchy process. The coal logistics node location examples show that the method proposed here has strong operability and broad applicability.